O corpo e o jornalismo cultural nos processos de mediação com o espectador - Gasparini, Igor (2015)
The main focus of this study is the cultural journalism crisis, that homogenizes culture and entertainment with severe consequences to the relation between spectator and artistic production. The goal is to investigate the cultural journalism in the analogical and digital medias, facing the emergent digital platforms developed by artists (Movimento 7x7, Discoreografia, and others). The aim is to check if the specific places dedicated to the dance communication are able to attract/cultivate/maintain the public interests, in a moment in which the segmentation is imposed as a form of coexistence. To investigate the relation between the individual with the art piece, the research is based on the Teoria Corpomídia (KATZ and GREINER, 2012). The communication piece‐spectator is worked considering the perspective proposed by MARTÍN‐BARBERO (2009), where the cultural journalism becomes a mediation; and the viewer is seen as an emancipated spectator, according to RANCIÈRE (2010). The studies of SCOTT TIMBERG (2015) about the artistic class, and the ones of PASCAL GIELEN (2013) about the creativity as a fundamentalism are also part of the theoretical foundation. The hypothesis is that the cultural journalism specialized in dance has already initiated a reinvention process, in order to face the increased silence on traditional medias. The methodology was concentrated in literature review, the analysis of a selected corpus and interviews with some of the agents of this context, namely, journalists, artists and curators of public cultural places